Perbedaan Berpikir Kritis Siswa Menggunakan Model Pembelajaran PBL Dan Inkuiri Terbimbing Pada Materi Elktrolit Dan Non Elektrolit - Robeka Hutasoit; Tita Juwitaningsih (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2023)
This study aims to determine differences in students' critical thinking using the Problem Based Learning (PBL) and Guided Inquiry learning models on electrolyte and non-electrolyte solutions. This research was conducted at SMAN 17 Medan in the 2022/2023 academic year. This type of research is a quasi-experimental research design with a pretest-posttest control group design. The population in this study were all students of class X IPA SMA Negeri 17 Medan. The sample of this study was class X IPA 5 as the experimental class I which was taught using the Problem Based Learning model and X IPA 6 as the experimental class II which was taught using the Guided Inquiry learning model. The results of this study indicate that there are differences in learning outcomes between the two classes with an average posttest score of students in experimental class I of 74 and an average posttest score of students in experimental class II of 82. The ability to think critically in experimental class I is prominent/dominant in analytical skills. The ability to think critically in experiment II is dominant in the ability to argue, evaluate and conclude.